Informal constructive culture and the transformation of caracas city neighborhoods (2009)
This work aims to expose some reflections about the popular constructive culture that has created an informal buildings consolidation system so that they are durable and can be converted into the heritage of several generations. This constructive culture of informal urbanization continues producing and transforming in a significant way housing urban space without achieving the standards of suitable housing and Habitat. A first reflection arises from conceiving the process of creating housing and Habitat popular in the barrios of Caracas as part of the cultural dynamics, understood as a process of interaction that occurs in a heterogeneous and unequal social context. Our second reflection goes to the way in which we perceive the housing consolidation process in the barrios. A way to look at cultural forms of popular sectors has been from their dependency relationships or secondary condition as regards with the dominant culture. Our position attends the shift to the paradigm that recognizes in the actions of neighborhood their ability to produce culture and new meanings of Habitat and housing production-related practices.